2021
DOI: 10.3390/ijerph182010727
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Caesarean Section Practice among Teenage Romanian Mothers Using Modified Robson Ten Group Classification System

Abstract: The Robson ten-group classification system is a recognized effective method of assessing caesarean rate. It is based on dividing patients into ten mutually exclusive groups, focusing on six maternal and newborn variables (parity, gestational age, plurality, foetal presentation, previous caesarean, and mode of labour onset). The aim of our analysis was twofold: first, to present the implementation of Robson classification in a pregnant teenage population; and second, to identify the indications for CS in the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…A personal obstetrician and educational level were substantially related to the obstetric recommendation for unnecessary CS, per research by Charoonwatana et al [22]. The main recipients to lower CS rates are adolescents in Robson group 1 [16].…”
Section: Konar Et Almentioning
confidence: 75%
See 1 more Smart Citation
“…A personal obstetrician and educational level were substantially related to the obstetric recommendation for unnecessary CS, per research by Charoonwatana et al [22]. The main recipients to lower CS rates are adolescents in Robson group 1 [16].…”
Section: Konar Et Almentioning
confidence: 75%
“…Active management of spontaneous onset of labour in a primigravida, lowering the primary CS delivery rate, following CS, and cautious case evaluation prior to inducing labour in nulliparous women are maybe a few helpful therapies [26]. Matei et al believe that future attention to obstetrical management in Robson groups 7 and 8 is essential [16]. A personal obstetrician and educational level were substantially related to the obstetric recommendation for unnecessary CS, per research by Charoonwatana et al [22].…”
Section: Konar Et Almentioning
confidence: 98%
“…The literature demonstrates controversial results related to the particularities of pregnancy evolution and birth in the adolescent population. Some studies report higher percentages of C-sections [ 41 , 42 , 43 ], some report similar C-section rates compared to adult pregnancies [ 44 , 45 , 46 ], and some studies report lower percentages of adolescent C-section birth [ 47 , 48 ]. As depicted in many previous studies, we observed a statistically significantly lower number of C-sections performed for various indications in the pregnant adolescent group when compared with pregnant women between 20 and 24 years old ( p -value less than 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…According to multiple studies, the rate of caesarean section in teenage pregnancies, especially primipara with more than 37 weeks of gestation, is 44.59%, exceeding the expectation of the World Health Organisation by almost 15% [9] [10].…”
Section: Introductionmentioning
confidence: 93%